(untitled) (Academicia Globe: Inderscience Research, 2023)
This article talks about the fact that educating young people in the spirit of patriotism is the main task to form the basis of upbringing, to shape the spirit of love for the motherland of young people in the later stages of education, to carry out spiritual and educational work in educational institutions.